Chinese Translation of Emily Dickinson’s Poetry: Translation Features of Shi Li’s Lilacs in the Sky - Zhou, Jianxin (International Journal of Language and Literary Studies, 2021)
Using program written in python language to conduct a statistical and comparative analysis of poetic form and vocabulary use of Emily Dickinson’s poems and its Chinese translation in the poetry collection, Lilacs in the Sky, translated by Shi Li, to reveal features of the translation. It is found that in translation, there is a large number of increases in stanzas and a relatively small adjustment in verse lines; a large number of dashes are omitted or translated into commas, and many commas are added, exclamation marks are basically deleted. Prepositions and conjunctions are used less frequently, making language structure less complete, and lyrical intensity is slightly inferior to the original. The less number of adjectives results in less delicate and less rich description in translation, but large increase in verbs and four-character words make translation more concrete, vivid and cordial. In short, the translation version deviates significantly from the original in terms of poetic form and vocabulary use, and the translation expression tends to be closer to the standard of Chinese poetry expression rather than to the source language.